Lacrimal intubation during dacryocystorhinostomy utilizing the STENTube. (2nd January 2017) - Shinder, Roman; Wu, Andrew; Mehendale, Reshma A.; Tang, Sunny X.; Nasser, Qasiem J.; Chou, Eva; Sniegowski, Matthew C.; Janda, Alexandra; Shepler, Todd R.; Blaydon, Sean M.; Nakra, Tanuj
ABSTRACT: The traditional use of the Crawford tube for lacrimal intubation during dacryocystorhinostomy (DCR) carries several drawbacks. We describe the use of the STENTube for DCR intubation and detail its advantages. Retrospective, noncomparative, interventional case series; 313 patients with nasolacrimal duct obstruction (NLDO) underwent 339 DCRs (216 external, 123 endonasal) with the STENTube from January 2007 – June 2013 by 5 surgeons (RS, QN, TS, SB, TN) across 3 institutions (SUNY Downstate Medical Center, Texas Oculoplastics Consultants, and Moorfields Eye Hospital). Study outcome measures included patient demographics, surgical complications, and epiphora improvement/resolution. 206 (66%) females and 107 (34%) males had a mean age of 63 years (range 2–94 years). Distribution of diagnoses included: 314 complete idiopathic acquired NLDO, 20 partial idiopathic acquired NLDO, and 5 congenital complete NLDO. 316 (93%) were primary DCRs and 23 (7%) were revisions. Epiphora improved in 312 (92%) cases with 294 (86%) experiencing resolution with patent lacrimal irrigation at a mean last follow-up of 9.4 months. Twenty-eight (8%) patients experienced surgical complications with 16 (5%) experiencing tube prolapse, and 20 (6%) requiring re-operation. The STENTube represents a simple method for lacrimal intubation during external or endonasal DCR at a comparable cost to the Crawford tube. It allows for low prolapse rates without the need for additional endonasal fixation procedures, resulting in a simple and comfortable post-operative extraction without risk of lacrimal trauma. The STENTube is our preferred intubation technique during DCR, and should be considered by oculofacial surgeons performing DCR with intubation.